Impacts of COVID-19 on the shift in e-commerce paradigm - Blažovský, Patrik; Pernica, Karel; Kubíček, Aleš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
The thesis aims to provide a comprehensive review of the researched topic in the form of a literature review and, by analyzing several available secondary data, draw a complex summary, thus, educate the reader by gaining insights on the environment of global e-commerce from the strategic point of view and analyze the consequences burdened by the global pandemics of COVID-19. Firstly, the author evaluates the global economy before and after massive disruptions following the pandemic outbreak and analyzes data regarding business performance and consumer behavior. The author will introduce and explain long-term strategic measures resulting from business challenges and opportunities for both customers and businesses and identifies critical strategic factors. The author also explains the importance of reshaping the business strategy with digitalization in mind as the essential foundation to become highly adaptive to meet customers’ changing needs. The thesis explains e-commerce as such with an additional focus on the retail sector within the industry. Even though global retail sales decreased significantly, e-commerce has, on the other hand, managed to grow faster than in previous years. The reason is mainly the convenience of online retail that the customers benefit from as a significant portion of added value. Although a shift from traditional commerce to the digital one is already happening, it is believed that the COVID crisis has accelerated the transformation by a couple of years. Should the consumers wanted or not, they have changed their behaviors to adapt to a new situation, so have the merchants. Ongoing trends supported by digitalization, such as the growing number of internet users or the rising usage of mobile devices, laid out perfect foundations for e-commerce to flourish in these difficult times.
The thesis, moreover, explains that such a shift in behavior is expected to cause permanent changes, which is, naturally, a positive sign of digital commerce.
Vedoucí práce: Karel Pernica
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses